REFINEMENT OF THE INTERVAL WITH ABRUPT CATAGENETICAL ALTERATIONS OF THE SEDIMENTARY ROCKS IN SOME OIL AND GAS FIELDS IN DDB - Karpenko, O.; Tunik, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article elaborates on the topic about abrupt catagenetical alterations in sedimentary rocks and postulates the topicality and problematics of the study during exploration of new and already existing oil and gas deposits. The goal of the research is the identification of compacted zone which was formed under secondary physical and chemical processes within 110–120 temperature interval (including possible paleotemperature effect). To get the most qualitative/comprehensive results, integrated analysis of lithology, petrophysical characteristics of cored intervals in the slide sections and geological information has been done by the authors. Essential part of the article is devoted to the methodology, study description and interpretation of outcome results. Four gas condensate fields were chosen based on their similarity. They have similar tectonic, structural, generation and accumulation conditions and all of them are located in the axial and pre-axial zone of the central part of Dnieper-Donets basin. After well log data processing and precise microscopy study of slide sections, the authors concluded that 110–120 temperature surfaces, which frame compacted and altered zone (identified by the Ukrainian Research Institute of Gas), have to be shifted according to new research findings. Practical value of this work is to identify compacted and decompacted zones at a great depth, which can be an indirect indicator of traps existence for hydrocarbons and possible manifestations of abnormal pressures.
Keywords: catagenesis; Lower Carboniferous; sandstone; siltstone; hydrocarbons; well logging; microscopy